Meri Dost - Naheed Hassan (Bookgroup, 2024)
"Meri Dost" by Naheed Hassan is an enchanting children's book that delves into the theme of friendship through a delightful narrative. The story follows the adventures of a young child and their best friend, capturing the essence of companionship and the joy that comes from having a close friend.
Keywords: Textbook -- Storybook